Association of progesterone receptor status with histopathological grading in patients with intracranial meningioma - Biswas, Pulak K.; Zahid Raihan, M.; Rahman, Khaled A.; Chowdhury, Aditi; Ahsan, Ashik (International Surgery Journal, 2026)
Background: Intracranial meningioma is a common primary brain tumor. Although most are benign, recurrence and variable behavior remain concerns. While World Health Organization (WHO) histopathological grading is an established prognostic tool, it does not always accurately predict tumor behavior. Progesterone receptor (PR) expression may serve as an additional prognostic marker. Objective of the study was to assess the association between progesterone receptor status and histopathological grading in patients with intracranial meningioma. Methods: This cross-sectional observational study was conducted in the Department of Neurosurgery, Bangladesh Medical University, Dhaka, Bangladesh from June 2018 to March 2020. A total of 35 patients with histologically confirmed intracranial meningioma were included. Clinical and radiological data were collected using a structured data sheet. Tumors were graded according to WHO classification. Progesterone receptor status was evaluated by immunohistochemistry and categorized based on percentage of nuclear positivity. Data were analyzed using statistical package for the social sciences (SPSS) version 22, and associations were tested using Fisher’s exact test. A p value <0.05 was considered statistically significant. Results: Among 35 patients, 88.57% had WHO grade I and 11.43% had grade II meningioma. A significant association was found between PR status and histopathological grade (p=0.013). Lower PR expression was more common in grade II tumors. No significant association was observed between PR status and tumor size. Conclusions: Progesterone receptor status is significantly associated with histopathological grading and may serve as an additional prognostic marker in intracranial meningioma.